Báo cáo kết quả tham dự Hội nghị toàn cầu Nghị sĩ trẻ IPU lần thứ 4 (Từ 17-18/11/2017, Ottawa, Canada) - Quốc hội (2017)
Báo cáo kết quả tham dự Hội nghị toàn cầu Nghị sĩ trẻ IPU lần thứ 4 (Từ 17-18/11/2017, Ottawa, Canada)